Sets in Excess Demand in Ascending Auctions with Unit-Demand Bidders - Tommy Andersson; Christer Andersson; Adolphus Johannes Jan Talman (Lund University, School of Economics and Management, Department of Economics, 2012)
This paper analyzes the problem of selecting a set of items whose prices are to be updated in the next iteration in so called simple ascending auctions with unit-demand bidders. A family of sets called "sets in excess demand" is introduced, and the main results demonstrate that a simple ascending auction always terminates at the minimum Walrasian equilibrium prices if and only if the selection belongs to this family. The paper also specifies a number of properties of the family of sets in excess demand and relate previously proposed selections to it.
Keywords: C62; D44; D50; 330; Multi-item auctions; unit-demand; excess demand; algorithms